Modi's Economics - Acharya, Rajeshkumar; Tanna, Girishchandra (Ahmedabad Nanoland, 2020)
Narendra Damodardas Modi, a Name buzzing across the world. It is his concrete work for development and welfare of all as Prime Minister that created a niche for himself in the hearts of the people within a short span of the years 2014-2019. This very sentiment that triggered us to write this book titled (3z(BModi's Economics(3y(B. In May 2014, a new government led by Prime Minister Narendra Modi took office. It was also the first time in India's history that the winning candidate had contested the national election predominantly on the platform of economic development. (3z(BSabka Saath, Sabka Vikas,(3y (Bwhich translates as (3z(BCollective Effort, Inclusive Development,(3y (Bwas the catch phrase When he took over as Prime Minister, the country was at the triplet of frustration, disappointment and demoralize. Prime Minister Modi took a different path, called Modi's Economics for the development of the country, which animated the country. The Book provides detailed discussion of all-round socio-economic development of the country in Modi regime. Schemes, Programmes and policies implemented by Modi Government are discussed in the Book at length. Unparallel visionary man Modi launched a programme (3z(BNew India@75 Sankalp se Siddhi(3y (Bmaking India a New India by 2022 on 75th year of Independence, is discussed in the Book. The Book pointedly evinces Narendra Modi's managerial skill, unique vision, dedication to the Nation and his commitment for welfare of all.s
Keywords: Tanna, Girishchandra; Economic policy; Politics and government; Economic development